Electricity storage element and all-solid-state secondary battery
By adjusting the void ratio in the electrode layer, the problem of degradation of performance of sintered all-solid-state secondary batteries in charge and discharge cycles is solved, and better cycle characteristics and longer service life are achieved.
Patent Information
- Application Number
- CN202380065261.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-12-21
- Filing Date
- 2023-12-06
- Publication Date
- 2025-04-25
AI Technical Summary
When the existing sintered all-solid-state secondary batteries are repeatedly charged and discharged, the charging and discharge performance is reduced, and the cycle characteristics are prone to deterioration.
In the thickness direction of the electrode layer, the void ratio of the first electrode layer portion is greater than that of the second electrode layer portion, thereby reducing the difference in expansion and contraction of the electrode layer, thereby suppressing the reduction of charge and discharge performance.
It effectively improves the cycle characteristics during charging and discharging of the secondary battery, reduces internal defects of the electrode layer, and extends the service life of the battery.
Smart Images

Figure CN119895620A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electric storage element and an all-solid-state secondary battery using the electric storage element. Background Art
[0002] Lithium-ion secondary batteries have established an indispensable position as a high-capacity and lightweight power source in mobile devices, electric vehicles, etc. However, existing lithium-ion secondary batteries mainly use flammable organic electrolytes as electrolytes, so there are concerns about the danger of fire. As a solution to this problem, the development of all-solid-state lithium-ion batteries using solid electrolytes instead of organic electrolytes is being promoted. However, due to concerns about the rising prices of global raw materials for lithium, the development of all-solid-state sodium-ion batteries is also being promoted.
[0003] In the following patent document 1, an all-solid-state secondary battery having a solid electrolyte sheet and an electrode layer formed on the surface of the solid electrolyte sheet is disclosed. Patent document 1 records that the solid electrolyte sheet has a second solid electrolyte layer formed on at least one surface of the first solid electrolyte layer. It is recorded that the second solid electrolyte layer is a porous solid electrolyte layer. It is recorded that the first and second solid electrolyte layers can be formed by firing a green sheet. In addition, in patent document 1, it is recorded that by making a part of the solid electrolyte sheet a porous layer, the close contact with the electrode layer can be improved.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: International Publication No. 2021 / 045039 Summary of the invention
[0007] Technical problem to be solved by the invention
[0008] However, when a sintered all-solid-state secondary battery formed by sintering a solid electrolyte layer and an electrode layer is repeatedly charged and discharged, there is a problem that the charge and discharge performance is reduced and the cycle characteristics are easily deteriorated.
[0009] An object of the present invention is to provide an electric storage element capable of improving the cycle characteristics of a secondary battery during charge and discharge, and an all-solid-state secondary battery using the electric storage element.
[0010] Technical solutions for solving technical problems
[0011] Each aspect of a power storage element and an all-solid-state secondary battery that solves the above-mentioned technical problems will be described.
[0012] The storage element of mode 1 of the present invention is characterized in that it includes: a solid electrolyte layer; an electrode layer, which is arranged on the main surface of one side of the solid electrolyte layer and contains an electrode active material and a solid electrolyte; and a collector layer, which is arranged on the main surface of the electrode layer on the opposite side of the solid electrolyte layer, wherein the porosity of a first electrode layer portion arranged at a position closer to the solid electrolyte layer than the center in the thickness direction of the electrode layer is greater than the porosity of a second electrode layer portion arranged at a position closer to the collector layer than the center in the thickness direction of the electrode layer.
[0013] In the electric storage device of aspect 2, in aspect 1, preferably, the porosity of the electrode layer increases from the current collector layer side toward the solid electrolyte layer side.
[0014] The storage element of embodiment 3 is preferably such that, in embodiment 1 or embodiment 2, when the solid electrolyte layer is a first solid electrolyte layer as a dense layer, the electrode layer is provided with an electrode material including an electrode active material and a solid electrolyte in a second solid electrolyte layer as a porous layer.
[0015] The power storage device of aspect 4 is preferably any one of aspects 1 to 3, wherein the solid electrolyte contains at least one selected from β″-alumina, β-alumina, and sodium super ion conductor (NASICON) crystals.
[0016] The electric storage device according to aspect 5 is preferably any one of aspects 1 to 4, wherein the solid electrolyte layer and the electrode layer are sintered bodies.
[0017] The all-solid-state secondary battery according to the sixth aspect of the present invention is characterized by comprising the power storage element according to any one of the first to fifth aspects.
[0018] Effects of the Invention
[0019] According to the present invention, it is possible to provide an electric storage element capable of improving the cycle characteristics of a secondary battery during charge and discharge, and an all-solid-state secondary battery using the electric storage element. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic cross-sectional view showing an electric storage element according to an embodiment of the present invention.
[0021] Figure 2 This is a schematic cross-sectional view of a case where an electrode layer in an electric storage device according to an embodiment of the present invention is divided into first to third electrode layer portions.
[0022] Figure 3 This is a schematic diagram showing an example of porosity distribution of an electrode layer in an electric storage device according to an embodiment of the present invention.
[0023] Figure 4 This is a schematic cross-sectional view showing an all-solid-state secondary battery according to one embodiment of the present invention. DETAILED DESCRIPTION
[0024] Hereinafter, preferred embodiments will be described. However, the following embodiments are merely illustrative, and the present invention is not limited to the following embodiments. In addition, in each of the drawings, components having substantially the same function are sometimes marked with the same reference numerals.
[0025] [Electrical storage element]
[0026] Figure 1 Schematic cross-sectional view showing an electric storage element according to an embodiment of the present invention. Figure 1 As shown, the power storage element 1 includes a solid electrolyte layer 2, an electrode layer 3, and a first current collector layer 4. The electrode layer 3 and the first current collector layer 4 are stacked in this order on a first main surface 2a of the solid electrolyte layer 2.
[0027] The electrode layer 3 includes an electrode active material 5 and solid electrolytes 6a and 6b. In the present embodiment, the electrode active material 5 is a positive electrode active material, and the electrode layer 3 is a positive electrode layer. However, in the present invention, the electrode active material 5 may also be a negative electrode active material, and the electrode layer 3 may also be a negative electrode layer.
[0028] The electrode layer 3 includes: a first electrode layer portion 3A disposed at a position closer to the solid electrolyte layer 2 than the center in the thickness direction of the electrode layer 3; and a second electrode layer portion 3B disposed at a position closer to the first current collector layer 4 than the center in the thickness direction of the electrode layer 3. In the present embodiment, the porosity of the first electrode layer portion 3A on the solid electrolyte layer 2 side is greater than the porosity of the second electrode layer portion 3B on the first current collector layer 4 side.
[0029] Among them, the porosity of the first electrode layer part 3A and the second electrode layer part 3B can be obtained by image analysis of the cross section along the thickness direction of the electrode layer 3. Image analysis, for example, can be performed by binarizing (converting to two colors, white and black) the electrode layer cross-sectional image obtained by scanning electron microscopy (SEM) and CT (computed tomography) using image processing software (such as ImageJ) to obtain the porosity. The threshold value during the binarization process is appropriately adjusted by observing the actual image while making the void portion black. The calculation of the porosity is performed by dividing the area (number of pixels) of the black part of each electrode layer divided area by the area (number of pixels) of the entire divided area.
[0030] Since the electric storage element 1 of the present embodiment has the above-described structure, the cycle characteristics of the secondary battery during charge and discharge can be improved.
[0031] In the prior art, in a sintered all-solid-state secondary battery formed by firing a solid electrolyte layer and an electrode layer, when charge and discharge are repeated, defects such as cracks are sometimes generated inside the storage element due to expansion and contraction of the electrode active material, resulting in reduced charge and discharge performance and deterioration of cycle characteristics.
[0032] In view of this, the inventors of the present invention focused on the fact that the charge and discharge reaction is more likely to proceed at the portion close to the solid electrolyte layer 2 in the thickness direction of the electrode layer 3, and the expansion and contraction of the electrode active material 5 becomes larger. It was found that by making the porosity of the first electrode layer portion 3A on the solid electrolyte layer 2 side greater than the porosity of the second electrode layer portion 3B on the first collector layer 4 side, the difference in expansion and contraction in the thickness direction of the electrode layer 3 can be reduced, and as a result, even if the charge and discharge cycle is advanced, it is possible to make it difficult for defects to occur inside the storage element 1, and it is possible to suppress the reduction in charge and discharge performance. Therefore, according to the storage element 1 of this embodiment, a secondary battery with excellent cycle characteristics during repeated charge and discharge can be provided.
[0033] In this embodiment, the porosity X of the first electrode layer portion 3A is preferably 30% by volume or more, more preferably 50% by volume or more, preferably 90% by volume or less, and more preferably 80% by volume or less. When the porosity X of the first electrode layer portion 3A is within the above range, the cycle characteristics of the secondary battery during repeated charge and discharge can be further improved.
[0034] The porosity Y of the second electrode layer portion 3B is preferably 20% by volume or more, more preferably 30% by volume or more, preferably 80% by volume or less, more preferably 60% by volume or less. When the porosity Y of the second electrode layer portion 3B is within the above range, the cycle characteristics of the secondary battery during repeated charge and discharge can be further improved.
[0035] The ratio (X / Y) of the porosity X of the first electrode layer portion 3A to the porosity Y of the second electrode layer portion 3B is preferably 1.01 or more, more preferably 1.05 or more, and preferably 10 or less, more preferably 3 or less. When the ratio (X / Y) is within the above range, the cycle characteristics of the secondary battery during repeated charge and discharge can be further improved.
[0036] In addition, if Figure 2 As shown, when the electrode layer 3 is divided into three equal parts in the thickness direction and the first electrode layer part 3C, the second electrode layer part 3D and the third electrode layer part 3E are formed in sequence from the solid electrolyte layer 2 side, it is preferred that the porosity increases in the order of the third electrode layer part 3E, the second electrode layer part 3D and the first electrode layer part 3C. Figure 3As shown, when the porosity of the electrode layer 3 has a gradient structure that increases from the first current collector layer 4 side toward the solid electrolyte layer 2 side, the cycle characteristics of the secondary battery during repeated charge and discharge can be further improved.
[0037] Furthermore, the porosity of the first electrode layer portion 3C, the second electrode layer portion 3D, and the third electrode layer portion 3E can also be determined by image analysis of a cross section along the thickness direction of the electrode layer 3 described above.
[0038] The porosity X of the first electrode layer portion 3C is preferably 30 volume % or more, more preferably 50 volume % or more, and is preferably 90 volume % or less, more preferably 80 volume % or less.
[0039] The porosity Y of the second electrode layer portion 3D is preferably 25 volume % or more, more preferably 40 volume % or more, and is preferably 85 volume % or less, more preferably 70 volume % or less.
[0040] The porosity Z of the third electrode layer portion 3E is preferably 20 volume % or more, more preferably 30 volume % or more, and is preferably 80 volume % or less, more preferably 60 volume % or less.
[0041] Hereinafter, the structure of each layer in the energy storage element 1 and other energy storage elements of the present invention will be described.
[0042] (Solid electrolyte layer)
[0043] The solid electrolyte constituting the solid electrolyte layer 2 is preferably formed of a sodium ion conductive oxide. As the sodium ion conductive oxide, there can be cited compounds containing at least one selected from Al, Y, Zr, Si and P, Na and O. As specific examples of sodium ion conductive oxides, there can be cited β-alumina or sodium superion conductor (NASICON) crystals with excellent sodium ion conductivity. Among them, the sodium ion conductive oxide is preferably at least one sodium ion conductive oxide selected from β"-alumina, β-alumina and sodium superion conductor crystals. The sodium ion conductive oxide is more preferably β-alumina or β"-alumina. Their sodium ion conductivity is more excellent.
[0044] β-alumina includes two types of crystals: β-alumina (theoretical composition formula: Na2O·11Al2O3) and β"-alumina (theoretical composition formula: Na2O·5.3Al2O3). β"-alumina is a quasi-stable substance, so materials with added Li2O and MgO as stabilizers are usually used. Compared with β-alumina, β"-alumina has a high sodium ion conductivity, so it is preferred to use β"-alumina alone or a mixture of β"-alumina and β-alumina, and it is more preferred to use Li2O-stabilized β"-alumina (Na 1.7 Li 0.3 Al10.7 O 17 ) or MgO stabilized β"-alumina ((Al 10.32 Mg 0.68 O 16 )(Na 1.68 O)).
[0045] As sodium superion conductor crystals, there are: Na3Zr2Si2PO 12 、Na 3.2 Zr 1.3 Si 2.2 P 0.8 O 10.5 、Na3Zr 1.6 Ti 0.4 Si2PO 12 、Na3Hf2Si2PO 12 、Na 3.4 Zr 0.9 Hf 1.4 Al 0.6 Si 1.2 P 1.8 O 12 、Na3Zr 1.7 Nb 0.24 Si2PO 12 、Na 3.6 Ti 0.2 Y 0.8 Si 2.8 O9、Na3Zr 1.88 Y 0.12 Si2PO 12 、Na 3.12 Zr 1.88 Y 0.12 Si2PO 12 、Na 3.05 Zr2Si 2.06 P 0.95 O 12 、Na 3.4 Zr2Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Mg 0.1 Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Zn 0.1 Si 2.4 P 0.6 O 12 、Na 3.4 Zr 1.9 Mg 0.1Si 2.2 P 0.8 O 12 、Na 3.4 Zr 1.9 Zn 0.1 Si 2.2 P 0.8 O 12 、Na 3.6 Zr 0.13 Yb 1.67 Si 0.11 P 2.9 O 12 、Na5YSi4O 12 Among them, the sodium superion conductor crystal is preferably Na 3.4 Zr2Si 2.4 P 0.6 O 12 Or Na 3.05 Zr2Si 2.06 P 0.95 O 12 In this case, the sodium ion conductivity can be further improved.
[0046] The solid electrolyte layer 2 can be manufactured by mixing raw material powders, shaping the mixed raw material powders, and then firing them. For example, it can be manufactured by slurrying the raw material powders to make green sheets, and then firing the green sheets. Alternatively, it can be manufactured by a sol-gel method.
[0047] The thickness of the solid electrolyte layer 2 is preferably 5 μm or more, more preferably 10 μm or more, further preferably 15 μm or more, preferably 1000 μm or less, more preferably 800 μm or less, and further preferably 500 μm or less. If the thickness of the solid electrolyte layer 2 is too thin, the mechanical strength is reduced and easily damaged, so it is easy to cause an internal short circuit. If the thickness of the solid electrolyte layer 2 is too thick, the sodium ion conduction distance accompanying the charge and discharge becomes longer, so the internal resistance becomes higher, and the discharge capacity and the operating voltage are easily reduced. In addition, when used for an all-solid-state secondary battery, the energy density per unit volume of the all-solid-state secondary battery is also easily reduced.
[0048] In the present embodiment, the solid electrolyte layer 2 is a first solid electrolyte layer as a dense layer. The porosity of the first solid electrolyte layer defined by the following formula (1) is preferably 20% or less, more preferably 10% or less, and further preferably 5% or less. The lower limit of the porosity is not particularly limited, and may be 0.1%, for example.
[0049] Void ratio = (1-p / p0) × 100 (%) ... Formula (1)
[0050] In formula (1), p is the volume density and p0 is the true density.
[0051] (Electrode layer)
[0052] The electrode layer 3 includes an electrode active material 5 and solid electrolytes 6a and 6b. In the present embodiment, the electrode layer 3 includes an electrode material disposed in a second solid electrolyte layer that is a porous layer.
[0053] The second solid electrolyte layer is composed of solid electrolyte 6a and is a porous layer having three-dimensionally connected voids. The porosity of the second solid electrolyte layer defined by the above formula (1) is preferably 25% or more, more preferably 30% or more, further preferably 40% or more, preferably 97% or less, more preferably 95% or less, further preferably 90% or less.
[0054] The electrode material includes an electrode active material 5 and a solid electrolyte 6b. The electrode material may include other materials such as a conductive auxiliary agent as required.
[0055] The content of the electrode active material 5 in the electrode layer 3 is not particularly limited, and is preferably 50% or more, more preferably 60% or more, preferably 99.9% or less, more preferably 95% or less, and further preferably 90% or less, in terms of mass%. When the content of the electrode active material 5 in the electrode layer 3 is within the above range, the capacity of the secondary battery can be further effectively increased.
[0056] The content of the solid electrolyte 6a, 6b in the electrode layer 3 is not particularly limited, and is preferably 0.1% or more, more preferably 5% or more, preferably 50% or less, more preferably 40% or less, and further preferably 30% or less, in terms of mass %. When the content of the solid electrolyte 6a, 6b in the electrode layer 3 is within the above range, the ion conductivity in the electrode layer 3 can be further improved, and the battery characteristics of the secondary battery can be further effectively improved. In addition, the content of the solid electrolyte 6a, 6b mentioned here refers to the total content of the content of the solid electrolyte 6a and the content of the solid electrolyte 6b.
[0057] When the electrode layer 3 contains a conductive auxiliary agent, the content of the conductive auxiliary agent is preferably 0.1% or more, more preferably 0.2% or more, preferably 20% or less, and more preferably 10% or less in terms of mass%. When the content of the conductive auxiliary agent in the electrode layer 3 is within the above range, high electron conductivity in the electrode layer 3 can be ensured, and ion conductivity can be further improved, and the battery characteristics of the secondary battery can be further effectively improved.
[0058] As the solid electrolytes 6a and 6b, the substances described in the section of the solid electrolyte layer 2 can be used. The solid electrolytes 6a and 6b are preferably the same type of solid electrolytes, but different types of solid electrolytes may be used in combination.
[0059] As the conductive additive, for example, conductive carbon can be used. Examples of conductive carbon include acetylene black, carbon black, Ketjen black, and vapor-grown carbon fiber (VGCF). The conductive additive is preferably a carbon-based conductive additive composed of the above materials.
[0060] In addition, in this embodiment, the electrode active material 5 is a positive electrode active material, and the electrode layer 3 is a positive electrode layer. However, in the present invention, the electrode active material 5 may be a negative electrode active material, and the electrode layer 3 may be a negative electrode layer. In addition, both the positive electrode layer and the negative electrode layer may be the electrode layer 3.
[0061] Positive active material:
[0062] The positive electrode active material is not particularly limited, but is preferably composed of a material having the general formula Na x M y P2O z A positive electrode active material composed of a crystal glass represented by (1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8, M is at least one selected from Fe, Ni, Co, Mn and Cr). Among them, a positive electrode active material composed of a crystal glass containing the general formula Na x A positive electrode active material composed of a crystal glass represented by MP2O7 (1≤x≤2, M is at least one selected from Fe, Ni, Co, Mn and Cr). As such a positive electrode active material crystal, for example, Na2FeP2O7, Na2CoP2O7, Na2NiP2O7, etc. can be used.
[0063] In addition, crystallized glass refers to a glass obtained by heating (firing) a precursor glass containing an amorphous phase to crystallize (crystallize). The amorphous phase can be completely transferred to the crystalline phase, or the amorphous phase can remain. In addition, one crystal can be precipitated, or more than two crystals can be precipitated. For example, crystallized glass can be judged by the peak angle represented by powder X-ray diffraction (XRD) to determine whether it is a crystallized glass.
[0064] Negative active material:
[0065] The negative electrode active material is not particularly limited, and for example, carbon electrode materials such as hard carbon and soft carbon can be used. The carbon electrode material is preferably hard carbon. Of course, the negative electrode active material may also include alloy negative electrode active materials such as tin, bismuth, lead, phosphorus, etc. that can absorb sodium, or metallic sodium.
[0066] Hereinafter, an example of a method for producing the electrode layer 3 will be described.
[0067] Manufacturing method of electrode layer:
[0068] First, a second solid electrolyte layer as a porous layer is formed on the first solid electrolyte layer as a dense layer. Such a first solid electrolyte layer and a second solid electrolyte layer can be formed according to the method for manufacturing a solid electrolyte sheet described in International Publication No. 2021 / 045039, for example.
[0069] Specifically, the first solid electrolyte layer and the second solid electrolyte layer can be formed, for example, according to a production method having the following steps a to d.
[0070] In step a, an organic vehicle containing a binder is added to at least one of the first solid electrolyte powder and the raw material powder of the first solid electrolyte powder to prepare a slurry, and the slurry is applied on a substrate and dried to obtain a green sheet for forming a first solid electrolyte layer.
[0071] In step b, an organic carrier containing a binder is added to a mixed powder containing a second solid electrolyte powder and at least one of the raw powders of the second solid electrolyte powder and a polymer powder to prepare a slurry, and the slurry is applied on a substrate and dried to obtain a raw sheet for forming a second solid electrolyte layer.
[0072] In step c, a second solid electrolyte layer forming green sheet is stacked on at least one main surface of the first solid electrolyte layer forming green sheet to obtain a stacked body.
[0073] In step d, the laminate is fired to form a first solid electrolyte layer as a dense layer and a second solid electrolyte layer as a porous layer.
[0074] Next, a paste containing an electrode active material precursor and solid electrolyte powder (the paste contains a conductive auxiliary agent as needed) is applied to the second solid electrolyte layer produced as a porous layer, and dried to form an electrode material layer. Thus, the electrode material layer is formed by the second solid electrolyte layer as a porous layer containing an immersion paste. In addition, the paste may contain an adhesive, a plasticizer, or a solvent as needed. Among them, the electrode material layer may also be a powder compact. Then, by firing the electrode material layer, the electrode layer 3 can be formed.
[0075] The drying temperature of the paste is not particularly limited, and may be, for example, 30° C. or higher and 150° C. or lower. The drying time of the paste is not particularly limited, and may be, for example, 5 minutes or higher and 600 minutes or lower.
[0076] The firing atmosphere is preferably a reducing atmosphere. The firing temperature (maximum temperature) can be, for example, 400° C. to 700° C., and the holding time at the temperature can be, for example, 5 minutes to less than 3 hours.
[0077] In this embodiment, for example, by adjusting the viscosity of the paste, in the obtained electrode layer 3 , the porosity of the first electrode layer portion 3A on the solid electrolyte layer 2 side can be made greater than the porosity of the second electrode layer portion 3B on the first collector layer 4 side.
[0078] In this case, the viscosity of the paste is preferably higher than that of the prior art. The viscosity of the paste is preferably 6000 mPa·s or more, more preferably 8000 mPa·s or more, and preferably 50000 mPa·s or less, more preferably 30000 mPa·s or less. The viscosity of the paste can be measured using a B-type viscometer.
[0079] However, in the present invention, when the second solid electrolyte layer is formed, the porosity of the first electrode layer portion 3A on the solid electrolyte layer 2 side can be made greater than the porosity of the second electrode layer portion 3B on the first collector layer 4 side by applying multiple layers of a slurry with different ratios of the void-forming material (polymer powder).
[0080] In addition, in the present embodiment, the electrode active material precursor is a positive electrode active material precursor. Of course, the electrode active material precursor may also be a negative electrode active material precursor. Hereinafter, the paste for forming the positive electrode layer when the electrode layer 3 is a positive electrode layer and the paste for forming the negative electrode layer when the electrode layer 3 is a negative electrode layer are described in detail.
[0081] Paste for forming positive electrode layer:
[0082] As the positive electrode layer forming paste, for example, a paste containing a positive electrode active material precursor and solid electrolyte powder can be used (the paste may further contain a conductive auxiliary agent as required). In addition, the paste may contain a binder, a plasticizer, or a solvent as required.
[0083] The positive electrode active material precursor (positive electrode active material precursor powder) is preferably composed of an amorphous oxide material that generates active material crystals by firing. When the positive electrode active material precursor powder is composed of an amorphous oxide material, active material crystals can be generated during firing, and softened and flowed to form a dense positive electrode layer. In addition, when the positive electrode layer contains a solid electrolyte, the positive electrode active material and the solid electrolyte can also be integrated. Alternatively, when the positive electrode layer is in contact with the solid electrolyte layer, the two can be integrated. As a result, an ion conduction path can be formed better, so it is preferred. In addition, in the present invention, "amorphous oxide material" is not limited to completely amorphous oxide materials, but also includes materials containing a portion of crystals (for example, a crystallinity of less than 10%).
[0084] The positive electrode active material precursor powder preferably contains 25% to 55% Na2O, 10% to 30% Fe2O3+Cr2O3+MnO+CoO+NiO, and 25% to 55% P2O5 in terms of mole % of oxide conversion. The reasons for limiting the composition are described below. In addition, in the following description of the content of each component, "%" means "mole %" unless otherwise specified.
[0085] Na2O is composed of the general formula Na x M y P2O z (M is at least one transition metal element selected from Cr, Fe, Mn, Co and Ni, 1≤x≤2.8, 0.95≤y≤1.6, 6.5≤z≤8) The main component of the active material crystal represented by the content of Na2O is preferably 25% to 55%, more preferably 30% to 50%. When the content of Na2O is within the above range, the charge and discharge capacity of the secondary battery can be further increased.
[0086] Fe2O3, Cr2O3, MnO, CoO and NiO are also composed of the general formula Na x M y P2O z The main component of the active material crystal represented by . The content of Fe2O3+Cr2O3+MnO+CoO+NiO is preferably 10% to 50%, more preferably 12% to 40%, and most preferably 15% to 30%. When the content of Fe2O3+Cr2O3+MnO+CoO+NiO is above the above lower limit, the charge and discharge capacity of the secondary battery can be further increased. On the other hand, when the content of Fe2O3+Cr2O3+MnO+CoO+NiO is below the above upper limit, it is possible to make it difficult for undesirable crystals such as Fe2O3, Cr2O3, MnO, CoO or NiO to precipitate. In addition, in order to further improve the cycle characteristics of the secondary battery, it is preferred to actively contain Fe2O3. The content of Fe2O3 is preferably 1% to 30%, more preferably 5% to 30%, further preferably 10% to 30%, and particularly preferably 15% to 25%. The content of each component of Cr2O3, MnO, CoO and NiO is preferably 0% to 45%, more preferably 10% to 40%, and further preferably 15% to 30%. In addition, when at least two components selected from Fe2O3, Cr2O3, MnO, CoO and NiO are contained, the total amount (total amount) is preferably 10% to 50%, more preferably 12% to 40%, and most preferably 15% to 30%.
[0087] P2O5 is also composed of the general formula Na x M y P2O zThe content of P2O5 is preferably 25% to 55%, more preferably 30% to 50%. When the content of P2O5 is within the above range, the charge and discharge capacity of the secondary battery can be further increased.
[0088] In addition to the above-mentioned components, the positive electrode active material precursor powder may also contain V2O5, Nb2O5, MgO, Al2O3, TiO2, ZrO2, or Sc2O3. These components have the effect of improving conductivity (electronic conductivity), and the rapid charge and discharge characteristics of the secondary battery are easily improved. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. When the content of the above-mentioned components is below the above-mentioned upper limit value, it is not easy to produce heterogeneous crystals that do not contribute to the battery characteristics, and the charge and discharge capacity of the secondary battery can be further increased.
[0089] In addition, the positive electrode active material precursor powder may contain SiO2, B2O3, GeO2, Ga2O3, Sb2O3, or Bi2O3 in addition to the above-mentioned components. By containing these components, the glass forming ability is further improved, and it is easy to obtain a more homogeneous positive electrode active material precursor powder. The content of the above-mentioned components is preferably 0% to 25% in total, and more preferably 0.2% to 10%. These components do not contribute to the battery characteristics, so when their content is too much, there is a tendency for the charge and discharge capacity of the secondary battery to decrease.
[0090] The positive electrode active material precursor powder is preferably produced by melting and molding a raw material batch. According to this production method, it is easy to obtain an amorphous positive electrode active material precursor powder with excellent homogeneity, so it is preferred. Specifically, the positive electrode active material precursor powder can be produced as follows.
[0091] First, raw materials are prepared in a manner to obtain a raw material batch in a desired composition. Then, the obtained raw material batch is melted (melted). The melting temperature is appropriately adjusted so that the raw material batch can be melted homogeneously. For example, the melting temperature is preferably above 800°C, more preferably above 900°C. The upper limit of the melting temperature is not particularly limited, but if the melting temperature is too high, it will lead to energy loss, evaporation of sodium components, etc., and is therefore preferably below 1500°C, more preferably below 1400°C.
[0092] The obtained molten material is then formed into a film by a method which is not particularly limited, and for example, the molten material may be flowed between a pair of cooling rolls and formed into a film while being rapidly cooled, or the molten material may be flowed into a casting mold and formed into an ingot.
[0093] Next, the obtained compact is pulverized to obtain a positive electrode active material precursor powder. The average particle size of the positive electrode active material precursor powder is preferably 0.01 μm or more and less than 0.7 μm, more preferably 0.03 μm or more and 0.6 μm or less, further preferably 0.05 μm or more and 0.6 μm or less, and particularly preferably 0.1 μm or more and 0.5 μm or less.
[0094] Binders are materials used to integrate raw materials (raw material powders) with each other. Examples of binders include cellulose derivatives such as carboxymethyl cellulose, hydroxypropyl methyl cellulose, hydroxypropyl cellulose, ethyl cellulose, hydroxyethyl cellulose, and hydroxymethyl cellulose, or water-soluble polymers such as polyvinyl alcohol; thermosetting resins such as thermosetting polyimide, phenolic resin, epoxy resin, urea-formaldehyde resin, melamine resin, unsaturated polyester resin, and polyurethane; polycarbonate resins such as polypropylene carbonate; and polyvinylidene fluoride.
[0095] Paste for forming negative electrode layer:
[0096] As a paste for forming a negative electrode layer, for example, a paste containing a carbon electrode material precursor and a solid electrolyte precursor can be used. When making the paste, first, prepare a solid electrolyte precursor. In addition, at this stage, it is preferred to prepare a solid electrolyte precursor solution. Specific examples of solid electrolyte precursors and their solutions are described later. Next, prepare a carbon electrode material precursor (a precursor of a carbon electrode material composed of hard carbon). Suitable sugars, biomass or polymers can be used in the carbon electrode material precursor.
[0097] Next, the solid electrolyte precursor solution and the carbon electrode material precursor are mixed and then dried. Thus, a powder of a mixture of the solid electrolyte precursor and the carbon electrode material precursor is obtained. Next, the powder of the above mixture is crushed and then mixed with a conductive auxiliary agent and a binder in an organic solvent. As an organic solvent, for example, N-methyl-2-pyrrolidone can be used. Thus, a paste is obtained.
[0098] When sugar is used as a carbon electrode material precursor, examples include sucrose, cellulose, D-glucose, sucrose, etc. When biomass is used as a carbon electrode material precursor, examples include corn stems, sorghum stems, pine cones, mangosteen, argan husks, rice husks, dandelions, the core of grain straw, ramie fiber, cotton, kelp, and the inner peel of coconut, etc. When a polymer is used as a carbon electrode material precursor, examples include PAN (polyacrylonitrile), asphalt, PVC (polyvinyl chloride) nanofibers, polyaniline, sodium polyacrylate, tires (tire polymers), phosphorus-doped PAN, etc.
[0099] When the solid electrolyte is β-alumina, the solid electrolyte precursor can be obtained by mixing aluminum nitrate, sodium nitrate, and lithium nitrate, for example. At this time, the ratio of the above-mentioned materials is adjusted to the target composition ratio of the solid electrolyte.
[0100] The solid electrolyte is a sodium superionic conductor crystal, Na5XSi4O 12 In the case of a solid electrolyte precursor solution, a solution containing sodium element and transition metal element and carbonate ion constituting the solid electrolyte can be cited as a solid electrolyte precursor solution. In addition, in the solution, the sodium element exists in the state of sodium ion, and the transition metal element exists in the state of transition metal ion. The solid electrolyte precursor is composed of a gelled substance or a dried substance of the solid electrolyte precursor solution, for example. Moreover, the above-mentioned solid electrolyte is composed of a sintered substance of the solid electrolyte precursor.
[0101] Alternatively, as the solid electrolyte precursor solution, a solution containing nitrate ions instead of carbonate ions may be used.
[0102] In addition, in the solid electrolyte precursor solution, the carbonate ion is preferably bidentately coordinated to the transition metal element. In this case, the transition metal element is likely to exist stably in the solution.
[0103] In addition, as a counter ion of the sodium ion, it is preferable to contain NR 4+ (In the formula, each R is independently selected from at least one substituent selected from H, CH3, C2H5, and CH2CH2OH.) In this way, the transition metal element can easily exist stably in the solution.
[0104] The solid electrolyte precursor solution can be obtained by mixing water glass (sodium silicate), sodium tripolyphosphate, and an aqueous solution of ammonium zirconium carbonate, for example.
[0105] As the binder, the binder described in the section of the positive electrode layer forming paste can be used.
[0106] Other details:
[0107] The thickness of the electrode layer 3 is preferably 5 μm or more, more preferably 20 μm or more, further preferably 50 μm or more, preferably 1000 μm or less, and more preferably 200 μm or less. When the thickness of the electrode layer 3 is above the above lower limit, the charge and discharge capacity of the secondary battery can be further improved. In addition, if the thickness of the electrode layer 3 is too thick, the resistance (resistance) to electron conduction becomes greater, and there is a decrease in the discharge capacity and operating voltage of the entire secondary battery. In addition, the stress caused by shrinkage during firing becomes greater, which can cause the problem of falling off.
[0108] (First Current Collector Layer)
[0109] The material of the first collector layer 4 is not particularly limited, and metal materials such as aluminum, titanium, silver, copper, stainless steel or their alloys can be used respectively. The above metal materials can be used alone or in combination. In addition, these alloys are alloys containing at least one of the above metals. The thickness of the first collector layer 4 is not particularly limited, and can be 0.01 μm or more and 1000 μm or less.
[0110] The formation method of the first current collector layer 4 is not particularly limited, and for example, physical vapor methods such as evaporation or sputtering, thermal CVD methods, MOCVD methods, chemical vapor methods such as plasma CVD methods, etc. can be cited. As other formation methods of the first current collector layer 4, plating, sol-gel methods, and liquid phase film forming methods based on spin coating can be cited. However, the first current collector layer 4 is preferably formed on the electrode layer 3 by sputtering because of its excellent adhesion.
[0111] [All-solid-state secondary battery]
[0112] Figure 4 Schematic cross-sectional view of an all-solid-state secondary battery according to one embodiment of the present invention. Figure 4 As shown, the all-solid-state secondary battery 10 includes an electric storage element 1 , a negative electrode layer 20 , and a second current collector layer 30 .
[0113] As described above, the storage element 1 includes: a solid electrolyte layer 2, an electrode layer 3 as a positive electrode layer provided on the first main surface 2a of the solid electrolyte layer 2, and a first collector layer 4 provided on the electrode layer 3. In addition, in the present embodiment, a negative electrode layer 20 is provided on the second main surface 2b of the solid electrolyte layer 2, and a second collector layer 30 is provided thereon. As the second collector layer 30, the structure described in the first collector layer column can be used.
[0114] Thus, in the present embodiment, the electrode layer 3 constituting the storage element 1 is a positive electrode layer. However, as described above, the electrode layer 3 may also be a negative electrode layer. In this case, the all-solid-state secondary battery 10 only needs to have a positive electrode layer on the second main surface 2b of the solid electrolyte layer 2 instead of the negative electrode layer 20. In addition, both the positive electrode layer and the negative electrode layer constituting the all-solid-state secondary battery 10 may also have the same structure as the electrode layer 3. In addition, the first collector layer 4, the second collector layer 30 and other collector layers only need to be provided on at least one side of the configuration electrode layer 3.
[0115] Since the all-solid-state secondary battery 10 of the present embodiment includes the electric storage element 1 , it is excellent in cycle characteristics when repeatedly charged and discharged.
[0116] Hereinafter, the present invention will be described in more detail based on specific examples, but the present invention is not limited to the following examples and can be implemented with appropriate changes within the scope of the present invention.
[0117] (Example 1)
[0118] (a) Preparation of Green Sheet for Forming First Solid Electrolyte Layer
[0119] Sodium carbonate (Na2CO3), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2), and yttrium oxide (Y2O3) were used as raw materials, and raw material powder was prepared in such a manner that, in terms of mol%, Na2O 14.2%, Al2O3 75.4%, MgO 5.4%, ZrO2 4.9%, and Y2O3 0.1%. After pre-sintering at 1250°C for 4 hours, the powder was pulverized so that the average particle size became 2 μm. Next, 100 parts by mass of the raw material powder obtained by pre-sintering and 12.5 parts by mass of polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "BM-SZ") as a binder were weighed, dispersed in N-methylpyrrolidone, and then fully stirred with a rotation-revolution mixer to form a slurry. The obtained slurry was applied onto a polyethylene terephthalate film (PET film) using a doctor blade, dried at 70° C., and then peeled from the PET film to obtain a green sheet for forming a first solid electrolyte layer.
[0120] (b) Preparation of Green Sheet for Forming Second Solid Electrolyte Layer
[0121] Sodium carbonate (Na2CO3), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2), and yttrium oxide (Y2O3) were used as raw materials, and raw material powder was prepared in such a manner that, in terms of mol%, Na2O 14.2%, Al2O3 75.4%, MgO 5.4%, ZrO2 4.9%, and Y2O3 0.1%, and was pre-calcined at 1250°C for 4 hours and then pulverized so that the average particle size became 2 μm. Next, 35 parts by mass of the raw material powder obtained by pre-calcination and 65 parts by mass of cross-linked polymethyl methacrylate particles (Sekisui Kasei Co., Ltd., product number "MBX-50", average particle size 50 μm) as polymer particles were weighed and mixed. 100 parts by mass of the obtained mixture and 12.5 parts by mass of a polyvinyl butyral resin (manufactured by Sekisui Chemical Co., Ltd., trade name "BM-SZ") as a binder were weighed, dispersed in N-methylpyrrolidone, and then fully stirred with a rotation-revolution mixer to form a slurry. The obtained slurry was applied to a PET film using a scraper, dried at 70°C, and peeled off from the PET film to obtain a green sheet for forming a second solid electrolyte layer.
[0122] (c) Preparation of laminate
[0123] The obtained second solid electrolyte layer forming green sheet was stacked on one main surface of the obtained first solid electrolyte layer forming green sheet, and isostatic pressing was performed at 90° C. and 40 MPa for 5 minutes to produce a laminate.
[0124] (d) Firing of laminated body
[0125] The obtained laminated body was fired at 1550° C. for 30 minutes to prepare a solid electrolyte layer (300 μm in thickness) in which the second solid electrolyte layer as a porous layer was provided on one main surface of the first solid electrolyte layer as a dense layer.
[0126] In the obtained solid electrolyte layer, the thickness of the first solid electrolyte layer was 200 μm, and the thickness of the second solid electrolyte layer was 100 μm. In addition, the porosity of the first solid electrolyte layer was 5%, and the porosity of the second solid electrolyte layer was 78%.
[0127] (e) Preparation of paste for forming positive electrode layer
[0128] Sodium metaphosphate (NaPO3), iron oxide (Fe2O3) and orthophosphoric acid (H3PO4) are used as raw materials. The raw material powders are prepared in a molar percentage so as to have a composition of 40% Na2O, 20% Fe2O3 and 40% P2O5, and melted at 1250°C in an air atmosphere for 45 minutes. Then, the melt is made to flow between a pair of rotating rollers and is formed while being rapidly cooled to obtain a film-like glass. The obtained film-like glass is crushed by a ball mill and a planetary ball mill, thereby obtaining an average particle size (D 50 ) was 0.2 μm glass powder (positive electrode active material precursor powder). In addition, the results of powder X-ray diffraction (XRD) measurement confirmed that the obtained glass powder was amorphous.
[0129] Weigh the obtained positive active material precursor powder 83% by mass, solid electrolyte powder 13% by mass, and acetylene black (TIMCAL, SUPERC65) 4% by mass as conductive carbon (conductive aid) respectively, and mix them for 30 minutes using agate mortar and pestle to make a positive composite material powder. Add 10 parts by mass of polypropylene carbonate (PPC) to 100 parts by mass of the produced positive composite powder, and further add 20 parts by mass of N-methylpyrrolidone. Use a rotation-revolution mixer to fully stir and slurry them, and make a paste for forming a positive electrode layer.
[0130] (f) Formation of positive electrode layer
[0131] On the main surface of the second solid electrolyte layer, an area of 1 cm 2、Capacity 1mAh / cm 2 The positive electrode layer forming paste was applied in a manner and dried at 70° C. for 3 hours to form a positive electrode material layer. The formed positive electrode material layer was fired at 525° C. for 30 minutes in a mixed gas atmosphere of 4 volume % H2 and 96 volume % N2, thereby forming a positive electrode layer on the main surface of one side of the solid electrolyte layer.
[0132] The viscosity of the positive electrode layer forming paste during application was 10000 mPa·s. The viscosity was measured at 25° C. using a B-type viscometer.
[0133] (g) Void ratio measurement
[0134] The porosity of the positive electrode layer is obtained by image analysis of the cross section along the thickness direction of the positive electrode layer. Image analysis is to obtain the porosity by binarizing the electrode cross-sectional image obtained by scanning electron microscope (SEM) using image processing software (Image J) (converting to two colors of white and black). The threshold value during binarization is determined by appropriately adjusting the gap portion to black while observing the actual image. The calculation of the porosity is performed by dividing the area (number of pixels) of the black portion of each electrode division area by the area (number of pixels) of the entire division area.
[0135] In addition, the porosity of the positive electrode layer is for a structure divided into two regions in the thickness direction ( Figure 1 ), divided into three regions ( Figure 2 ) were measured respectively. For the structure divided into two regions, the porosity X (volume %) of the first electrode layer part and the porosity Y (volume %) of the second electrode layer part were measured in the thickness direction from the solid electrolyte layer side. In addition, for the structure divided into three regions, the porosity X (volume %) of the first electrode layer part, the porosity Y (volume %) of the second electrode layer part and the porosity Z (volume %) of the third electrode layer part were measured in the thickness direction from the solid electrolyte layer side.
[0136] (h) Current collector formation and button cell assembly
[0137] A 100nm thick aluminum vapor-deposited film was formed on the entire surface of the positive electrode layer as a current collector. Then, in an argon glove box with a dew point below -60°C, metallic sodium, which became the negative electrode layer, was crimped onto the main surface of the solid electrolyte layer on the opposite side of the positive electrode layer and sealed in a CR2032 button cell to produce an all-solid-state secondary battery.
[0138] (i) Charge and discharge cycle test
[0139] The all-solid-state secondary battery was vacuum sealed with an aluminum laminated outer body. Then, a charge and discharge cycle test was performed (charging: 0.1C / 4.5V CC / CV 0.02C cutoff, 25°C, discharging: 0.1C CC 1.5V cutoff, 25°C), and the discharge capacity retention rate after 100 cycles relative to the initial discharge capacity (capacity retention rate after 100 cycles) was obtained.
[0140] (Comparative Example 1)
[0141] Except that the viscosity of the positive electrode layer forming paste during application was 5000 mPa·s, an all-solid secondary battery was prepared in the same manner as in Example 1 and a charge-discharge cycle test was performed.
[0142] (Comparative Example 2)
[0143] Except that the viscosity of the positive electrode layer forming paste during application was 3000 mPa·s, an all-solid secondary battery was prepared in the same manner as in Example 1 and a charge-discharge cycle test was performed.
[0144] The results are shown in the following Table 1. In Table 1, the units of X, Y, and Z are volume %.
[0145] [Table 1]
[0146]
[0147] Description of Reference Numerals
[0148] 1……Electrical storage element
[0149] 2…Solid electrolyte layer
[0150] 2a, 2b... first and second main surfaces
[0151] 3...Electrode layer
[0152] 3A, 3C... First electrode layer
[0153] 3B, 3D...Second electrode layer
[0154] 3E... The third electrode layer
[0155] 4……First current collector layer
[0156] 5……Electrode active substances
[0157] 6a, 6b...Solid electrolyte
[0158] 10……All-solid-state secondary battery
[0159] 20……Negative electrode layer
[0160] 30: second current collector layer.
Claims
1. A power storage element, characterized in that: include: Solid electrolyte layer; an electrode layer, which is disposed on a main surface of one side of the solid electrolyte layer and comprises an electrode active material and a solid electrolyte; and a current collector layer provided on a main surface of the electrode layer on the opposite side to the solid electrolyte layer, The porosity of the first electrode layer portion arranged at a position closer to the solid electrolyte layer than the center of the electrode layer in the thickness direction is greater than the porosity of the second electrode layer portion arranged at a position closer to the collector layer than the center of the electrode layer in the thickness direction.
2. The electric storage element according to claim 1, characterized in that: The porosity of the electrode layer increases as it goes from the current collector layer side to the solid electrolyte layer side.
3. The electric storage element according to claim 1 or 2, characterized in that: When the solid electrolyte layer is a first solid electrolyte layer as a dense layer, the electrode layer is formed by arranging an electrode material including an electrode active material and a solid electrolyte in a second solid electrolyte layer as a porous layer.
4. The electric storage element according to claim 1 or 2, characterized in that: The solid electrolyte contains at least one selected from β"-alumina, β-alumina and sodium superion conductor crystals.
5. The electric storage element according to claim 1 or 2, characterized in that: The solid electrolyte layer and the electrode layer are sintered bodies.
6. An all-solid-state secondary battery, characterized in that: A power storage element according to claim 1 or 2.
Citation Information
Patent Citations
Solid electrolyte sheet and method for producing same
WO2021045039A1